International Student Engagement: Strategies for Creating Inclusive, Connected, and Purposeful Campus Environments - Barnett III, Clyde (Journal of International Students, 2016)
International Student Engagement: Strategies for Creating Inclusive, Connected, and Purposeful Campus Environments is an in-depth analysis of seven colleges and universities across the United States, examining unique programs and activities for international students that foster belonging and connectedness on campus. This book provides a snapshot into the ways institutions effectively engage with international students. The authors examine the effectiveness of programs and policies intended to assist international students through research findings and by examining first-hand student experiences. For higher education/student affairs professionals, this book is an excellent resource to help move higher education institutions forward and into a space that promotes inclusivity.